1962
DOI: 10.1103/physrev.128.1783
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Matrix Elements in the First-Forbidden Beta Decay of theEu152Ground State

Abstract: The degree of circular polarization P c (6p y ) and the directional correlation W(0p y ) = 1+^2(^)^2(00^7) were measured in the 3~(1.49-MeV jS~) -> 2 + (0.344-MeV 7) ->0 + /3-7 cascade leading from the ground state of Eu 152 to the Sm 152 ground state. The angle d$ y is the angle between the £ and 7 momentum vectors. Representative values of P c (0p y ) measured at W=3.20 (in units mc 2 ) for some average angles 6$ y are: P c (90°) = -0.01=b0.09, P c (130°) = +0.33±0.07, P c (157°)-0.33±0.07, P«(171°)=0.24±0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1963
1963
1983
1983

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…which is in agreement with the results of Alexander and Steffen (1962) and Appalacharyulu et al (1969) A reorientation is observed in the 122 keY level of 15ZSm and we find…”
Section: Decay Scheme Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…which is in agreement with the results of Alexander and Steffen (1962) and Appalacharyulu et al (1969) A reorientation is observed in the 122 keY level of 15ZSm and we find…”
Section: Decay Scheme Resultssupporting
confidence: 94%
“…This result has been corrected for fourth order effects. Several authors (Alexander and Steffen 1962;Appalacharyulu et al 1969) have performed /3-y angular correlation and polarization measurements of this cascade. Their results have been expressed in terms of the Kotani (1959) parameters Y, x, U, z.…”
Section: Decay Scheme Resultsmentioning
confidence: 99%
See 1 more Smart Citation